2007
DOI: 10.1017/s0007485307005202
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal mortality factors of the coffee leafminer,Leucoptera coffeella

Abstract: Seasonal population fluctuation of the coffee leafminer, Leucoptera coffeella (Guérin-Méneville & Perrottet) (Lepidoptera: Lyonetiidae), led to an investigation of its natural mortality factors during the rainy season when the population level is low and during the dry season when population peaks occur. Life-table data were collected from insecticide-free plots within a 3 ha coffee plantation on the upper, medium and lower canopy. Leafminer mortality was similar among the canopy parts but varied in the two se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 37 publications
3
91
0
11
Order By: Relevance
“…Previous studies have addressed the influences of environmental (rainfall, relative humidity, ambient temperature, etc.) on coffeeleaf-miner population dynamics (REIS et al, 2006;PEREIRA et al, 2007, LOMELÍ-FLORES, 2010. For example, PEREIRA et al (2007) have suggested that heavy rain was the main source of coffee-leaf-miner mortality, particularly during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the influences of environmental (rainfall, relative humidity, ambient temperature, etc.) on coffeeleaf-miner population dynamics (REIS et al, 2006;PEREIRA et al, 2007, LOMELÍ-FLORES, 2010. For example, PEREIRA et al (2007) have suggested that heavy rain was the main source of coffee-leaf-miner mortality, particularly during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was carried out at the Experimental Station of Epamig, in the municipality of Oratórios (20°24'S, 42°48'W), MG, Brazil, from May to August 2007, during part of the region's dry season and under favorable climate conditions for L. coffeella (Pereira et al, 2007). Five lime sulphur concentrations (0.5, 1.0, 1.5, 2.0, and 2.5%, v/v) were applied either biweekly or monthly.…”
Section: Methodsmentioning
confidence: 99%
“…These measures include the use of nonsynthetic products approved by national organic standard organizations. In Brazil, organic coffee growers often spray a large array of organic farming-compatible products aiming at controlling the coffee leaf miner Leucoptera coffeella Guérin-Mèneville (Lepidoptera: Lyonetiidae), one of the key coffee pests (Reis et al, 2002;Pereira et al, 2007). Among organic farming-compatible products used for organic coffee production are botanical extracts, biofertilizers, sulphur based products and Bordeaux mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Para a avaliação das densidades do bicho mineiro e das vespas predadoras contou-se o número de minas ativas (presença de larvas vivas do bicho mineiro) e o número de minas predadas (presença de rasgaduras ocasionadas pelas vespas predadoras nas faces adaxial e abaxial da folha) pelos principais gêneros de vespas predadoras de L. coffeella encontradas em cafeeiros nessa região, Mischocyttarus, Polistes, Protopolybia, Polybia, Brachygastra e Protonectarina (Pereira et al 2007). A contagem das minas ativas e predadas foi realizada através da abertura das minas com estilete metálico.…”
Section: Methodsunclassified